Pelaksanaan Pengembangan Keprofesian Berkelanjutan Guru Kelas SD Negeri 2 Tarakan - ., Maksum (Program Studi Magister Pedagogi, 2015)
Pelaksanaan Pengembangan Keprofesian BerkelanjutanGuru Kelas SD Negeri 2 TarakanMaksumGuru SMPN 7 TarakanEmail: makdasari@gmail.comAbstract:This research objective was to know the implementation of continual professional development of homeroom teachers at public elementary school cluster 2 Tarakan. This research used descriptive qualitative method. The result showed that continual professional development had not been implemented entirely. A strong support had been given by principal but teacher’s motivation was still less. The supporting factors of the implementation of continual professional development for homeroom teachers at public elementary school in cluster 2 Tarakan were a strong motivation from principal, the head of cluster and local department of education, and the availability of transportation budget and registration funding to attend training, workshop, seminar, teacher’s working group, and other trainings. Meanwhile, the inhibiting factors are the lack of homeroom teacher’s motivation, the lack of socialization, teachers are difficult to follow the development of internet communication and technology, and teacher does not attempt to develop his competency, insufficient facility and infrastructure.Keywords: sustainable professionalism development, teacher’s professionAbstrak:Penelitian ini bertujuan untuk mengetahui pelaksanaan PKB guru kelas SDN di gugus 2 Tarakan menggunakan metode kualitatif deskriptif. Hasil penelitian ini adalah PKB belum terlaksana secara menyeluruh. Dukungan kuat telah diberikan oleh kepala sekolah namun motivasi dari guru itu sendiri yang masih kurang. Faktor pendukung pelaksanaan PKB bagi guru kelas SDN di gugus 2 Tarakan adalah motivasi yang kuat dari kepala sekolah, ketua gugus dan dinas pendidikan kota, serta tersedianya anggaran transportasi dan biaya pendaftaran untuk mengikuti diklat, lokakarya, seminar, KKG, dan pelatihan lainnya. Sedangkan faktor penghambatnya adalah kurangnya motivasi dari diri guru kelas itu sendiri, kurangnya sosialisasi, sulit guru mengikuti perkembangan TIK, tidak berupaya mengembangkan kompetensi dirinya, kurang memadainya sarana prasarana yang ada.Kata Kunci: pengembangan keprofesian berkelanjutan, profesi guru